Potential impact of financial innovation on financial services and monetary policy - Marek Dabrowski (Center for Social and Economic Research (CASE), 2017)
The recent wave of financial innovation, particularly innovation related to the application of information and communication technologies, poses a serious challenge to the financial industry's business model in both its banking and non-banking components. It has already revolutionised financial services and, most likely, will continue to do so in the future. If not responded to adequately and timely by regulators, it may create new risks to financial stability, as occurred before the global financial crisis of 2007-2009. However, financial innovation will not seriously affect the process of monetary policymaking and is unlikely to undermine the ability of central banks to perform their price stability mission.
Keywords: E41; E44; E51; E52; E58; G21; 330; monetary policy; financial innovation; electronic money